Empirical Test of Put - call Parity on the Standard and Poor’s 500 Index Options (SPX) over the Short Ban 2008 - Do, Huyen (VNU Journal of Science: Policy and Management Studies, 2017)
Put call parity is a theoretical no-arbitrage condition linking a call option price to a put option price written on the same stock or index. This study finds that Put call parity violations are quite symmetric over the whole sample. However during the ban period 2008 in the U.S., puts are significantly and economically overpriced relative to calls. Some possible explanations are the short selling restriction, momentum trading behaviour and the changes in supply and demand of puts over the short ban. One interesting finding that the relationship between time to expiry, put call parity deviations and returns on the index is highly non-linear. Key word: Put-call parity, SPX, short ban 2008 .